Renal function: filtration and clearance - Briffa, Jessica (Henry Stewart Talks, 2024)
Overview of renal clearance, Inulin clearance, Urea clearance, Penicillin clearance, Autoregulation, Tubuloglomerular feedback, Renin-angiotensinogen-aldosterone system in blood pressure regulation, Sympathetic nervous system activation in blood pressure regulation, Atrial natriuretic peptide in blood pressure regulation